Televisão e sociabilidade : os pequenos estabelecimentos comerciais de Pelotas/RS - Rosa, Guilherme Carvalho da (2014)
This research aims to comprehend the role of television in sociability between customers, employees and owners of small business in Pelotas, in the state of Rio Grande do Sul (Brazil). This empirical qualitative research was conducted in two popular food business establishments, a restaurant and a bar, all located in downtown. The first concern was to watch and describe the use of television in each of the chosen places and the sociability that occurs in all of them. Later, for interpretation purposes, the concern was defined in the meanings assigned to the sociability. Finally, the research sought to map the moments when the television participated in the place s sociability considering the theoretical perspective adopted, particularly the mediation model by Jesús Martín-Barbero, the idea of habitus by Pierre Bourdieu and the application of this category to the context of peripheral modernity by Jessé Souza. Within the theoretical and methodological framework, the research was conducted with the combination of two techniques:! observation/participation of the researcher, as a customer, and interviews with informers from the three social roles considered for this research; the owners, the employees and the customers. As a final consideration, it was possible to notice the preponderance of television for small business as decisive , considering its potency in the dynamics of sociability. It was also possible to notice the idea that the sociability related to the television needs to consider the crossing of social class dispositions that operate directly on the comprehension of limits for this social form, taking as a starting point its definition in Georg Simmel.